A novel gastroretentive floating system for zidovudine, based on calcium-silicate beads - Yoshida, Valquíria M. H. [UNESP]; Granato, Elis; Gremião, Maria Palmira Daflon [UNESP]; Balcão, Victor M.; Vila, M. M. D. C.; Oliveira Júnior, José M.; Severino, Patrícia; Souto, Eliana B; Chaus, Marco Vinícius (Academic Journals, 2013)
The aim of the research effort entertained herein was to develop, evaluate and fully characterize a multiparticulate floating gastroretentive system for the modified release of zidovudine (AZT), an antiretroviral drug. AZT was used as a water-soluble model drug at therapeutic doses. The floating gastroretentive system was obtained via polymer coating of calcium silicate-adsorbed AZT. The proposed system was evaluated in vitro for particle micromorphology, lag time for floating and duration of floating, drug loading capacity, drug release profile, and drug release kinetics. The physicochemical properties of AZT were evaluated by scanning electron microscopy (SEM) analyses, differential scanning calorimetry (DSC) analyses, X-ray diffraction (XRD) analyses, and infrared spectroscopy (FTIR) analyses. Results from SEM analysis of the AZT-containing floating gastroretentive granules allowed observation of an irregular surface and the apparent absence of pores. Floating of the AZT-containing gastroretentive granules was immediately achieved, that is lag time for floating was virtually zero and duration of floating was higher than 12 h. The drug loading capacity of the floating gastroretentive granules was ca. 81.09 ± 14.66%, and the release system thus obtained exhibited an extended drug release profile. Results from DSC and XRD analyses showed a modification in the AZT solid state, while the FTIR spectroscopy analyses revealed that the chemical structure of AZT remained unchanged upon adsorption to calcium silicate followed by polymeric coating. Hence, the coated granules produced presented gastroretentive, floating, and extended drug release properties.
Keywords: Zidovudine; Cal-sil floating granules; Gastroretentive floating system; Extended drug release; Zidovudine (AZT); Polymer coating